The effectiveness of STEM based mathematics Learning media in enhancing students higher order thinking skills - Sukmawati, R Ati; Pramita, Mitra; Saputra, Novan Alkaf Bahraini (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to address this issue by examining the effectiveness of interactive STEM-based mathematics learning media in enhancing students higher-order thinking skills compared to conventional instructional approaches. Method: This study employed a quantitative approach using a quasi-experimental design with a non-equivalent pretest posttest control group. The participants consisted of eighth grade students divided into an experimental group and a control group. The experimental group was taught using interactive STEM-based mathematics learning media, while the control group received conventional, teacher centered instruction. Students higher order thinking skills were assessed using HOTS-oriented test instruments developed based on the Revised Bloom’s Taxonomy. Data analysis was conducted using normalized gain (N-gain) scores and inferential statistical tests to determine the magnitude and significance of learning improvements. Findings: The results indicate that students in the experimental group showed significantly greater improvement in higher-order thinking skills than those in the control group. The experimental group achieved a high normalized gain score (N-gain = 0.77), whereas the control group attained a moderate gain score (N-gain = 0.64). Further analysis revealed that the most notable improvements occurred in the analysis and evaluation indicators, while gains in the creation indicator remained at a moderate level. Significance: These findings provide empirical evidence that interactive STEM-based mathematics learning media effectively supports the development of students’ higher-order thinking skills by promoting active engagement, independent learning, and contextual problem solving. This study highlights the potential of STEM integration as a strategic approach to fostering essential 21st-century cognitive competencies in mathematics education.